The Influence of Accounting Knowledge, Internal Control, and Financial Literacy on the Financial Performance of Boarding Houses: (Study on Boarding House Owners in Bengkalis District) - Meri Marfina; Rosmida Rosmida (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study is driven by the significance of effective financial management in boarding houses, so boarding house owners need to have adequate where accounting knowledge, internal control systems, and financial literacy to improve their financial performance. This study aims to examine the effect of accounting Knowledge, Internal Control, and Financial Literacy on the financial performance of boarding houses in Bengkalis District. The research method a quantitative research design, with data obtained using structured questionnaires distributed to 68 owners or kost managers, and the analysis was carried out using descriptive statistical analysis, instrument validity and reliability assessments, classical assumption evaluations, and multiple linear regressions through SPSS, The findings of this study indicate that simultaneously the three independent variables jointly exerted a statistically significant influence on Financial Performance, with a significance level below 28.598 and a p < 0.001 and an Adjusted R² of 0.553. Partially, Internal Control (β = 0.164; p < 0.001) and Financial Literacy (β = 0.542; p < 0.001) had demonstrated a positive and statistically meaningful impact, whereas Accounting Knowledge did not show a significant effect (β = –0.134; p = 0.108). These findings show that the application of internal control mechanisms and financial literacy has a stronger role in improving financial performance than just accounting knowledge that is not applied optimally. This study recommends increasing internal control training, financial literacy, and practical bookkeeping assistance for boarding house owners to strengthen business performance.